Incorporating movement breaks into primary school classrooms; a mixed methods approach to explore the perceptions of pupils, staff and governors - Rebecca A. Chorlton; Craig A. Williams; Sarah Denford; Bert Bond (BMC, 2022)
Abstract Background Public health guidelines for children advocate physical activity (PA) and the restriction of continuous sedentary time. Schools offer an attractive setting for health promotion, however school-based interventions to increase PA typically fail, and primary school children may spend most of the school day sitting down. Classroom movement breaks have been identified as an attractive opportunity to address this concern and may positively influence behaviour, but little is known about the barriers to implementing movement within lessons from a multi stakeholder perspective. The purpose of this study was to explore (1) the perceptions of primary school pupils, staff members and governors regarding classroom movement breaks, and (2) their perceived barriers and facilitators to implementing PA into the classroom. Methods Thirty-four pupils (Key Stages 1 and 2, ages 5-7 y) took part in a focus group discussion. Sixty-four staff members and twenty governors completed a questionnaire and an optional follow up semi-structured telephone interview. Qualitative data were analysed using thematic analysis. Results Pupils, staff members and governors expressed an enthusiasm for movement breaks provided that they were short, simple, pupil-guided and performed at the discretion of the teacher. Time and concerns regarding transitioning back to work following a movement break were identified as key barriers by pupils and staff. Governors and some staff expressed that favourable evidence for movement breaks is needed to facilitate their adoption, particularly regarding the potential for improvements in cognitive functioning or classroom behaviour. Conclusion There is a wide appeal for classroom-based activity breaks, when delivered in a manner that is not disruptive. Future research which examines the potential benefits of such activity breaks is warranted.